Negotiating the personal in creative writing - Vandermeulen, Carl (New writing viewpoints., 2011)
This book describes an alternative way to teach Creative Writing, one that replaces the silent writer taking criticism and advice from the teacher-led workshop with an active writer who reflects upon and publically questions the work-in-progress in order to solicit response, from a writers' group as well as from the teacher. Both accompany the writer, first as readers and fellow writers, only later as critics. Because writers ask, they listen, and dialogues with responders become an inner dialogue that guides later writing and revision. But when teachers accompany writers, teaching CW becomes.